Ionic liquid electrolytes for room temperature sodium battery systems. (20th May 2019) - Brutti, S.; Navarra, M.A.; Maresca, G.; Panero, S.; Manzi, J.; Simonetti, E.; Appetecchi, G.B.
Abstract: Safer electrolytes for ambient temperature sodium batteries were prepared by blending the N -butyl- N -methylpyrrolidinium bis(trifluoromethylsulfonyl)imide, PYR14 TFSI, ionic liquid with the sodium bis(trifluoromethylsulfonyl)imide, NaTFSI, salt. The physicochemical as well as the electrochemical properties of the PYR14 TFSI-NaTFSI binary electrolyte system were investigated as a function of the temperature and sodium salt mole fraction, and compared with those of organic electrolytes of interest for sodium batteries. A plethora of characterization techniques were adopted ranging from density, viscosity and conductivity measurements, thermogravimetry and electrochemical methods (linear sweep voltammetry, transference number, galvanostatic experiments). Preliminary galvanostatic cycling tests were carried out in Na/NaMnO2 cells at room temperature. The results are presented and discussed in the present paper. Highlights: PYR14 TFSI-NaTFSI mixtures as safer electrolytes for sodium battery systems. Fast ion transport properties, showing a VTF behaviour, at low temperatures. Thermally stabile above 200 °C. Electrochemical stability window exceeding 4 V in carbon working electrodes. Initial capacity exceeding 130 mA h g −1 in Na/NaMnO2 cells.